PENGARUH LAMA PERENDAMAN KEDELAI DAN PROPORSI TEPUNG BERAS SEBAGAI UPAYA MENINGKATKAN MUTU GIZI TEMPE - Suparno Suparno; Giyanto Giyanto; Wijantri Kusumadati; Agus Sadono (Agrienvi: Jurnal Ilmu Pertanian, 2020)
The purpose of this research was to determine the effect of long soaking soybeans and rice flour proportion of the N amino levels and organoleptic properties of soybean tempeh. Experimental design used in this research is randomized factorial design with the first factor that is long soaking 4, 8, 12, and 16 hours and the second factor is the proportion of rice flour, 3, 6, and 9 gram/1000 grams of soybean, each treatment is repeated 4 (four) times. The results showed that treatment of long soaking gives significant effect on pH soybean tempeh, moisture content, N-amino, the number of lactic acid bacteria, and organoleptic texture, taste, and smell. While the proportion of rice flour treatment significantly effect the water content tempeh, and their interaction had no significant effect on any parameters tested. The best treatment for the manufacture of soybean tempeh is on a long soaking 8 hours and the proportion of rice flour 6 gram/1000 grams of Soybean materials. Keywords: long soaking, the proportion of rice flour and soybean tempeh